2002
DOI: 10.1093/jpepsy/27.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Collecting and Managing Multisource and Multimethod Data in Studies of Pediatric Populations

Abstract: We emphasize the utility of multisource and multimethod data and provide recommendations for future work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
201
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(210 citation statements)
references
References 68 publications
4
201
1
4
Order By: Relevance
“…Our results confirm some studies that state that children's age can affect their and their parents' perceptions of the child's health and well-being [10]. Additionally, as children's cognitive abilities mature and grow closer to the level of their parents, ratings of different subscales may change depending on the developmental stage of the child [12,23,30]. Moreover, Jozeflak et al [22] studied QoL scores of healthy school children and their parents and found a low to moderate concordance between total QoL using KINDL.…”
Section: 00supporting
confidence: 86%
“…Our results confirm some studies that state that children's age can affect their and their parents' perceptions of the child's health and well-being [10]. Additionally, as children's cognitive abilities mature and grow closer to the level of their parents, ratings of different subscales may change depending on the developmental stage of the child [12,23,30]. Moreover, Jozeflak et al [22] studied QoL scores of healthy school children and their parents and found a low to moderate concordance between total QoL using KINDL.…”
Section: 00supporting
confidence: 86%
“…Future research could extend the analyses to include parents' views on the socialisation climate they offer to their children. Earlier research has shown that the correlations between adolescents and their parents on this type of measure are in the low-to-moderate range (Holmbeck, Li, Schurman, Friedman, & Coakley, 2002). Direct observation of enabling and constraining behaviours in family interactions (Yasui & Dishion, 2008) could also yield additional information on adolescent-parent relationships.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…De studie is daarmee een van de eerste op dit onderzoeksgebied die simultaan de percepties van moeders, vaders, oudere en jongere broers/zussen bestudeert. Het meenemen van meerdere perspectieven binnen een gezin is belangrijk omdat ouders en kinderen verschillende percepties kunnen hebben over opvoeding (zie ook Holmbeck, Li, Schurman, Friedman & Coakley, 2002). Bijvoorbeeld, adolescenten ervaren dat ze veel minder vaak praten over roken en minder op een goede en respectvolle manier dan dat de ouders dit ervaren (Harakeh, Scholte, De Vries & Engels, 2005).…”
Section: Huidige Studieunclassified
“…Bijvoorbeeld, adolescenten ervaren dat ze veel minder vaak praten over roken en minder op een goede en respectvolle manier dan dat de ouders dit ervaren (Harakeh, Scholte, De Vries & Engels, 2005). Daarnaast kunnen deze verschillende percepties over opvoeding verschillende effecten hebben op het rookgedrag van adolescenten (Holmbeck, Li, Schurman, Friedman & Coakley, 2002).…”
Section: Huidige Studieunclassified